Forearm bone mineral density in postmenopausal Indian women: correlation with calcium nutrition - Sharma, Swati; Agarwal, Bhavna; Sharma, Rohit; Singh, Simarpreet (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Osteoporosis is characterized by low bone mass with micro architectural deterioration of bone tissue leading to enhanced bone fragility, thus increasing the susceptibility to fracture. This study was conducted with the objective of measuring forearm bone mineral density in postmenopausal Indian women and to establish a correlation with indices of calcium nutrition i.e. dietary calcium intake, calcium supplements, serum calcium, serum phosphorus, serum alkaline phosphatase and serum intact parathyroid hormone. Methods: Fifty healthy, ambulatory postmenopausal women were selected and a prospective observational study was conducted to correlate the BMD with indices of calcium nutrition. Patient’s laboratory investigations (serum calcium, serum phosphorous, serum alkaline phosphatase and serum intact parathyroid hormone were done and BMD was assessed with dual-energy X-ray absorptiometry at non-dominant forearm; T-scores and Z-score were derived. Correlation analysis was done to investigate the relationship between indices of calcium nutrition and BMD. Results: The proportion of osteoporosis in forearm was 22%in the deficient group, 60% in the insufficient group and 18% in the sufficient group. Among the study group 15 subjects were osteoporotic by T score mid forearm where as 7 were osteoporotic with T score ultra distal forearm and 11 subjects had osteoporosis with T score total forearm. Conclusions: Out of all the indices of calcium nutrition, the correlation between the serum alkaline phosphatase and T score forearm was statistically significant.